Civilization and its discontents - Freud, Sigmund, 1856-1939; Strachey, James; Gay, Peter, 1923-2015 (New York : W.W. Norton & Company, 1989)
A translation of a 1929 text in which Freud summarized his views on culture from a psychoanalytic perspective
Editor's introduction / James Strachey -- Civilization and its discontents / Sigmund Freud -- Sigmund Freud: A brief life / Peter Gay
Translation of: Das Unbehagen in der Kultur
Includes bibliographical references (pages 113-118) and index
Translation of: Das Unbehagen in der Kultur
Keywords: Psychoanalysis and culture; Civilization; Civilization